A COMPARATIVE ANALYSIS OF RECRUITMENT STRATEGIES IN THE IT SECTOR AND IT CONSULTING FIRMS - Pallavi Sinha Dr. Smriti Tiwari (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2024)
This study aimed to do a comparative analysis of the recruitment strategies used by IT sector enterprises and IT consulting organizations, emphasizing the problems, methods, and areas for development. Through surveys and interviews with IT and consulting organizations situated in Rajasthan, the study collected data from one hundred respondents. In order to attract and retain top people and preserve competitiveness, the research closes by highlighting the significance of coordinating recruitment tactics with company objectives, streamlining procedures, and managing resources efficiently. The study also sought to offer advice to organizational executives, recruiters, and HR specialists on how to improve their hiring practices. The study examined a variety of aspects of recruitment dynamics, including demographic profiles, common methodologies, difficulties like drawn-out interview processes, and perceptions regarding external recruitment sources and organizational reputation. It did this by using a mixed method approach that included surveys, interviews, industry reports, and literature reviews. The results show that, in the highly competitive IT industry, effective talent acquisition and retention depend on a strategic alignment between recruitment tactics and business objectives.